Release behavior of dichlorprop from zn/al-ldh-dichlorprop nanocomposite into chloride, carbonate and phosphate solutions - Norhayati Hashim (Tanjong Malim, 2019)
Release behavior of dichlorprop from zn/al-ldh-dichlorprop nanocomposite into chloride, carbonate and phosphate solutions by Norhayati Hashim